2017
DOI: 10.1200/jco.2017.35.15_suppl.1008
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of pembrolizumab (pembro) monotherapy for previously treated metastatic triple-negative breast cancer (mTNBC): KEYNOTE-086 cohort A.

Abstract: 1008 Background: In KEYNOTE-012, pembro showed durable activity and manageable safety in patients (pts) with PD-L1+ mTNBC. Cohort A of KEYNOTE-086 (NCT02447003) examined the efficacy/safety of pembro in previously treated mTNBC, regardless of PD-L1 expression. Methods: Pts with centrally confirmed mTNBC, ≥1 prior chemotherapy for metastatic disease, and ECOG PS 0-1 had pembro 200 mg Q3W for up to 24 mo; imaging q 9 wk for the first 12 mo, then q 12 wk. Clinically stable pts with PD could remain on pembro unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
113
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 0 publications
4
113
2
1
Order By: Relevance
“…37 Results have been reported for cohorts A and B, but not yet for cohort C. For the 170 previously treated patients enrolled in cohort A, RR was 4.7% regardless of PD-L1 positivity, with 1 CR and 7 PRs. 36 In subgroup analyses, objective response rate (ORR) was improved in patients with a low tumour burden, normal LDH at baseline and non-visceral disease and appeared independent of PD-L1 expression. Preliminary results for the first 52 untreated patients preselected based on PD-L1 expression enrolled in cohort B revealed an ORR of 23.1%, whereas stable disease (SD) (≥24 weeks) and PD were observed in 17% and 58% of the patients, Solinas respectively.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…37 Results have been reported for cohorts A and B, but not yet for cohort C. For the 170 previously treated patients enrolled in cohort A, RR was 4.7% regardless of PD-L1 positivity, with 1 CR and 7 PRs. 36 In subgroup analyses, objective response rate (ORR) was improved in patients with a low tumour burden, normal LDH at baseline and non-visceral disease and appeared independent of PD-L1 expression. Preliminary results for the first 52 untreated patients preselected based on PD-L1 expression enrolled in cohort B revealed an ORR of 23.1%, whereas stable disease (SD) (≥24 weeks) and PD were observed in 17% and 58% of the patients, Solinas respectively.…”
Section: Introductionmentioning
confidence: 98%
“…ICB agents targeting inhibitory molecules expressed on the surface of immune cells, such as cytotoxic T lymphocyte antigen-4 (CTLA-4), programmed death-1 (PD-1) or its ligand, the programmed death-ligand 1 (PD-L1) expressed by both tumour and immune cells, have been evaluated in several early-phase trials in BC. [31][32][33][34][35][36][37][38][39][40][41] In the metastatic setting, these drugs showed promising results as single agents, with higher response rates (RRs) observed in the TNBC subtype, 32 PD-L1-positive tumours 32 33 and also in combination with chemotherapy (CT). 35 38 More recent studies have revealed that the PD-1/PD-L1 blockade combined with CT in the neoadjuvant setting increases pathological complete response (pCR) rates with manageable safety profiles in TNBC and HER2-negative BC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 27 evaluable patients with a median of 2 prior therapies for metastatic disease, the objective response rate was 18.5% [58]. The subsequent KEYNOTE-086 Phase II trial evaluated pembrolizumab in metastatic TNBC patients that were previously treated with any level of PD-L1 expression (Cohort A) and as 1st line treatment in patients with PD-L1+ status (Cohort B) [59]. Among 170 patients enrolled in cohort A, 105 (61.8%) had PD-L1+ status and 43.5% had received 3 or more prior lines of therapy.…”
Section: Targeting the Pd-1/pd-l1 Checkpoint In Tnbcmentioning
confidence: 99%
“…In this trial, tumors were considered PD-L1-positive when PD-L1 was expressed in 5% of the infiltrating immune cells. The clinical activity of pembrolizumab in this subset has been confirmed by the analysis of an extended cohort of BC patients (n = 170) with an ORR of 23% in the first-line setting [14]. However, it is noteworthy that the efficacy of PD-(L)1 inhibitors in BC as a single agent appears to be modest.…”
Section: Pd-1/pd-l1 As a Therapeutic Targetmentioning
confidence: 85%